Event related potentials reveal that increasing perceptual load leads to increased responses for target stimuli and decreased responses for irrelevant stimuli - Rorden, Chris; Guerrini, Chiara; Swainson, Rachel; Lazzeri, Marco; Baylis, Gordon C. (Frontiers in Human Neuroscience, 2008)
Lavie and colleagues (1995, JEP:HPP 9: 497-) have suggested that perceptual processing is influenced by perceptual load. Specifically, relevant information receives additional processing in high load situations exhausting the available capacity. On the other hand, irrelevant information receives less processing with increasing load on a relevant task, as there is a reduced amount of residual processing available. Rees et al. (1997, Science 278: 1616-) provided the first physiological evidence for this model, showing this pattern in a functional magnetic resonance imaging (fMRI) study. Likewise, Handy et al. (2001, Psych Sci 12: 213-) offered supporting evidence measuring event related potentials (ERPs). Both of these studies presented irrelevant information in peripheral vision. Here we manipulated load while using the identical stimuli and the same task (a peripheral gap judgment task) with centrally presented irrelevant stimuli. Event related potentials show the pattern predicted by Lavie and colleagues, specifically for the N1 component. This work offers further evidence that visual attention modulates relatively early processing of perceptual information. Specifically, increasing load resulted in stronger N1 responses to relevant information and weaker N1 responses to irrelevant information.